Time saving, simple and reproducible method to quantify left ventricular function in patients with atrial fibrillation. (25th November 2020) - Bunting, K.V; Gill, S; Sitch, A; Mehta, S; O'Connor, K; Hodson, J; Lip, G.Y.H; Stanbury, M; Kirchhof, P; Griffith, M; Townend, J.N; Steeds, R.P; et al.
Abstract: Introduction: Echocardiography is essential for the management of patients with atrial fibrillation (AF), but current methods are time consuming and lack any evidence of reproducibility. Purpose: To compare conventional averaging of consecutive beats with an index beat approach, where systolic and diastolic measurements are taken once after two prior beats with a similar RR interval (not more than 60 ms difference). Methods: Transthoracic echocardiography was performed using a standardized and blinded protocol in patients enrolled into the RAte control Therapy Evaluation in permanent AF randomised controlled trial (RATE-AF; NCT02391337). AF was confirmed in all patients with a preceding 12-lead ECG. A minimum of 30-beat loops were recorded. Left ventricular function was determined using the recommended averaging of 5 and 10 beats and using the index beat method, with observers blinded to clinical details. Complete loops were used to calculate the within-beat coefficient of variation (CV) and intraclass correlation coefficient (ICC) for Simpson's biplane left ventricular ejection fraction (LVEF), global longitudinal strain (GLS) and filling pressure (E/e'). Results: 160 patients (median age 75 years (IQR 69–82); 46% female) were included, with median heart rate 100 beats/min (IQR 86–112). For LVEF, the index beat had the lowest CV of 32% compared to 51% for 5 consecutive beats and 53% for 10 consecutive beats (p<0.001). The index beat also had the lowest CV for GLS (26% versus 43% and 42%; p<0.001) and E/e' (25% versus 41% and 41%; p<0.001; see Figure for ICC comparison). Intra-operator reproducibility, assessed by the same operator from two different recordings in 50 patients, was superior for the index beat with GLS bias −0.5 and narrow limits of agreement (−3.6 to 2.6), compared to −1.0 for 10 consecutive beats (−4.0 to 2.0). For inter-operator variability, assessed in 18 random patients, the index beat also showed the smallest bias with narrow confidence intervals (CI). Using a single index beat did not impact on the validity of LVEF, GLS or E/e' measurement when correlated with natriuretic peptides. Index beat analysis substantially shortened analysis time; 35 seconds (95% CI 35 to 39 seconds) for measuring E/e' with the index beat versus 98 seconds (95% CI 92 to 104 seconds) for 10 consecutive beats (see Figure). Conclusion: Index beat determination of left ventricular function improves reproducibility, saves time and does not compromise validity compared to conventional quantification in patients with heart failure and AF. After independent validation, the index beat method should be adopted into routine clinical practice. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Institute of Health Research UK